Growth Differentiation Factor-15 (GDF-15) Levels Are Associated with Cardiac and Renal Injury in Patients Undergoing Coronary Artery Bypass Grafting with Cardiopulmonary Bypass - Kahli, Abdelkader; Guenancia, Charles; Zeller, Marianne; Grosjean, Sandrine; Stamboul, Karim; Rochette, Luc; Girard, Claude; Vergely, Catherine (PloS one, 2014)
Growth differentiation factor-15 (GDF-15) has been identified as a strong marker of cardiovascular disease; however, no data are available concerning the role of GDF-15 in the occurrence of organ dysfunction during coronary artery bypass grafting (CABG) associated with cardiopulmonary bypass (CPB). Five arterial blood samples were taken sequentially in 34 patients from anesthesia induction (IND) until 24 h after arrival at the intensive care unit (ICU). Plasma levels of GDF-15, follistatin-like 1 (FLST1), myeloperoxidases (MPO), hydroperoxides and plasma antioxidant status (PAS) were measured at each time-point. Markers of cardiac (cardiac-troponin I, cTnI) and renal dysfunction (neutrophil gelatinase-associated lipocalin, NGAL) and other classical biological factors and clinical data were measured. Plasma GDF-15 levels increased gradually during and after surgery, reaching nearly three times the IND levels in the ICU (3,075±284 ng/L vs. 1,061±90 ng/L, p<0.001). Plasma MPO levels increased dramatically during surgery, attaining their highest level after unclamping (UNCLAMP) (49±11 ng/mL vs. 1,679±153 ng/mL, p<0.001) while PAS significantly decreased between IND and UNCLAMP (p<0.05), confirming the high oxidative status induced by this surgical procedure. ICU levels of GDF-15 correlated positively with cTnI and NGAL (p = 0.006 and p = 0.036, respectively), and also with hemoglobin and estimated glomerular filtration rate (eGFR). Among all the post-operative biomarkers available, only eGFR, NGAL and GDF-15 measured at ICU arrival were significantly associated with the onset of acute kidney injury (AKI). Patients with a EuroSCORE >3 were shown to have higher GDF-15 levels. During cardiac surgery associated with CPB, GDF-15 levels increased substantially and were associated with markers of cardiac injury and renal dysfunction.